The puppet carver - Cawthon, Scott 1971-; Cooper, Elley (Cawthon, Scott 1971- Five nights at Freddy's. Fazbear frights, 2021)
Five Nights at Freddy's fans won't want to miss this pulse-pounding collection of three novella-length tales that will keep even the bravest FNAF player up at night. Consumed by failure... Desperate to keep his kiddie pizzeria from bankruptcy, Jack lets his animatronics tech pitch him a new invention that might just give him some perspective. Frustrated by an unfair arcade game, Colton throws himself into re-engineering the device at any cost. Marley's best friend goes missing on a tour of the Freddy's Pizza Factory; she knows what really happened... but her guilt isn't the only thing threatening to eat her alive. In this ninth volume, Five Nights at Freddy's creator spins three sinister novella-length stories from different corners of his series' canon.